Floristic diversity of the Tropical Rainforest in Mexico - José Luis Villaseñor; Enrique Ortiz-Bermúdez; Jorge A. Meave (Botan‪ical Sciences)
Background: The tropical rainforest (TRF) is a type of vegetation recognized for its species diversity and the degree of human threat to which it is subjected. In America, its northernmost distribution is in Mexico, but its floristic knowledge in the country is still fragmentary.